Psychometric Properties of the revised piper fatigue scale in Greek women with breast cancer - Theodosopoulou, Eleni; Tzavelas, George; Kotrotsiou, Evangelia; Anastasiou, N.; Konstadinou, Evangelos; Raftopoulos, Vasilios (My University, 2001)
The aim of this research was the assessment of reliability, validity and responsiveness of the Revised Piper Fatigue Scale (RPFS) in Greek women with breast cancer. A total number of 174 cancer patients were interviewed and completed the RPFS. The mean age of the sample was 56.5±12.2 years old. Factor analysis confirmed the multidimensionality of the RPFS, associated with 4 factors/subscales. The RPFS has a high internal consistency (Cronbach’s a= 0,91). The mean fatigue score is independent of the place of permanent residence (p=0.14), and the occupation (p=0.26). There is no statistically significant difference of the scores among the education levels (p=0.23) and among the marital status (p=0.47). There is a weak linear relation (r=0.116) between the overall score and the age. There is also a strong linear relation between the fatigue score and the Langer score (r=0.76). Future research plans could include the comparison of the various breast cancer therapies in terms of the fatigue level and the investigation of whether the same scale applies for other type of cancer.
Keywords: RPFS; Validity; Fatigue; Reliability; Breast--Cancer